Confidence analysis of design and cost performance for solvent-based CO2 capture from a cement plant: a stochastic modeling perspective - Kuncheekanna, Vishalini Nair; Gardarsdottir, Stefania; Roussanaly, Simon (Frontiers in Chemical Engineering, 2025)
This study seeks to understand the impact of uncertainties in the solvent property submodel on the design and cost of the solvent-based CO2 capture process. First, a deterministic model of the MEA-based CO2 capture process using the CEMCAP reference cement plant case was developed and validated in the CO2SIM flowsheet simulator. Subsequently, a stochastic approach using the Monte Carlo simulation framework was applied by coupling the validated process model and UQLab, a MATLAB-based uncertainty quantification toolbox. Based on this, the implications of these uncertainties on key performance indicators are derived: CO2 capture ratio, specific reboiler duty, reboiler duty, condenser duty, lean rich heat exchanger duty, and lean and rich loading. Finally, the impact of these uncertainties on equipment design and the CO2 avoidance cost are assessed and discussed. The results show that heat exchanger duty uncertainty falls within the overdesign margin commonly used in engineering practice. However, the CO2 avoidance cost exhibits significant uncertainty linked to solvent properties (∼5.2%) that are mainly linked to uncertainty in the CO2 capture ratio. Hence, a key element in reducing CO2 avoidance cost uncertainty may be to validate suitable absorber height to guarantee, with a reasonable confidence, a 90% capture ratio via pilot testing.